2016
DOI: 10.1111/ceo.12867
|View full text |Cite
|
Sign up to set email alerts
|

Hidden mechanisms beyond the pupillary block in acute angle closure: ultrasound biomicroscopic study

Abstract: The most common mechanism contributing to AAC development in this Thai population was iridolenticular wrapping. From this study, we suggest that iridolenticular wrapping was the most common hidden mechanism beyond pupillary block among Thai patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…Their results indicated that the most common occurrence mechanism of APAC was PB (35%), followed by TPIR (26%), PIC (23%), and ELV (17%). Through an analysis of UBM images, Suwan et al [27] found that besides the PB mechanism (23.6%), the main underlying nonpupillary block mechanism was the antedisplacement of the lens-iris diaphragm (including the crowded-angle mechanism and anterior lens subluxation mechanism) (68.1%), followed by the plateau iris mechanism. In another study, Wang et al [28] utilised UBM for the observation of anatomical structures related to the chamber angle and they found that the angle closure mechanisms for PACG can be classified as follows: (1) pupillary block factors (38.1%), (2) nonpupillary block factors (7.1%), and (3) combination of multiple mechanisms (54.8%).…”
Section: Discussionmentioning
confidence: 99%
“…Their results indicated that the most common occurrence mechanism of APAC was PB (35%), followed by TPIR (26%), PIC (23%), and ELV (17%). Through an analysis of UBM images, Suwan et al [27] found that besides the PB mechanism (23.6%), the main underlying nonpupillary block mechanism was the antedisplacement of the lens-iris diaphragm (including the crowded-angle mechanism and anterior lens subluxation mechanism) (68.1%), followed by the plateau iris mechanism. In another study, Wang et al [28] utilised UBM for the observation of anatomical structures related to the chamber angle and they found that the angle closure mechanisms for PACG can be classified as follows: (1) pupillary block factors (38.1%), (2) nonpupillary block factors (7.1%), and (3) combination of multiple mechanisms (54.8%).…”
Section: Discussionmentioning
confidence: 99%
“…Because of this, UBM is an ideal modality for evaluation of ciliary body pathology, small tumors in particular [49][50][51]. UBM has also been useful in identifying structural morphologies contributing to glaucoma, such as iris plateau syndrome [52]. These examples illustrate how high frequency, high resolution ultrasonic biomicroscopy can practically be applied to ocular evaluation and how this imaging can change practice and drive innovation.…”
Section: Ultrasound Use In Ophthalmologymentioning
confidence: 99%
“…It is difficult to determine the zonular compromise in eyes with AAC attack before surgery. The role of the anteriorly positioned lens is an important factor in causing the acute angle closure [4,5]. Except for anteriorly positioned lens, differentiating the differences of anatomic features is helpful to precisely diagnose the eyes with lens subluxation induced AAC and to avoid missed diagnosis.…”
Section: Introductionmentioning
confidence: 99%